Cerebellum and neurodevelopmental disorders: RORα is a unifying force - Ribeiro, Svethna; Sherrard, Rachel M. (Frontiers in Cellular Neuroscience, 2023)
Errors of cerebellar development are increasingly acknowledged as risk factors for neuro-developmental disorders (NDDs), such as attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and schizophrenia. Evidence has been assembled from cerebellar abnormalities in autistic patients, as well as a range of genetic mutations identified in human patients that affect the cerebellar circuit, particularly Purkinje cells, and are associated with deficits of motor function, learning and social behavior; traits that are commonly associated with autism and schizophrenia. However NDDs, such as ASD and schizophrenia, also include systemic abnormalities, e.g. chronic inflammation, abnormal circadian rhythms etc, which cannot be explained by lesions that only affect the cerebellum. Here we bring together phenotypic, circuit and structural evidence supporting the contribution of cerebellar dysfunction in NDDs and propose that the transcription factor Retinoid-related Orphan Receptor alpha (RORalpha) provides the missing link underlying both cerebellar and systemic abnormalities observed in NDDs. We present the role of RORalpha in cerebellar development and how the abnormalities that occur due to RORalpha deficiency could explain NDD symptoms. We then focus on how RORalpha is linked to NDDs, particularly ASD and schizophrenia, and how its diverse extra-cerebral actions can explain the systemic components of these diseases. Finally, we discuss how RORalpha-deficiency is likely a driving force for NDDs through its induction of cerebellar developmental defects, which in turn affect downstream targets, and its regulation of extracerebral systems, such as inflammation, circadian rhythms and sexual dimorphism.